THE EFFECT OF TESTOSTERONE DEPRIVATION ON ATHEROPLAQUE FORMATION, TESTOSTERONE RECEPTORS, AND COLLAGENIZATION IN WISTAR PENILE TISSUE - Azrul, Imam Dirgantara; Tigor, Aaron; Sugandi, Suwandi; Hernowo, Betthy S. (Indonesian Journal of Urology, 2012)
Objective: To evaluate the association between testosterone deprivation and atheroplaque formation, testosterone receptors, and collagenization in Wistar penile tissues. Material & method: Two months after orchiectomized bilaterally, penile tissue of eight Wistar were harvested for semi-quantitative analysis of atheroplaque formation using hematoxyllin-eosin staining. Similar analysis were also conducted to look for collagenization by collagenase staining as well as the expression of testosterone receptors by immunohistochemistry staining. Control group were eight Wistar underwent Sham surgery. Statistical analysis for atheroplaque formation in Wistar compare to control group used was Chi-square, Fishers’ exact test was used for the expression of testosterone receptors, and independent t-tests for evaluating collagenization. Results: A significant decline in the testosterone receptors and increase collagenization were obtained in orchiectomized Wistar, while atheroplaque formation was not significantly different. Conclusion: Testosterone deprivation revealed a significant decline in the expression of testosterone receptors, and a significant increase in collagenization while atheroplaque formation was not significantly changed. Keywords: Erectile dysfunction, testosterone receptors, collagenization, atheroplaque formation, orchiectomy.